A survey of motorhomes and key factors to consider when developing electric motorhomes. Issue 2 (24th March 2019) - Chand, Praneel
Electric vehicles are becoming a popular choice for daily travel due to their cheaper running costs and reduced impact on climate change. Recently, companies are starting to show interest in the design and development of electric recreational vehicles for the tourism and leisure market. Hence, this paper reviews the current motorhome market in New Zealand focussing on the country's largest motorhome provider. Following this, some existing electric motorhomes or prototypes and conversions currently available in the world are reviewed. Some of the key factors of electric motorhome design are presented and their relationship to major components in an electric vehicle is analysed. The drivetrain configuration, battery, and electric motor must be selected to work in harmony in order to maximise the benefits of moving to an electric or hybrid system.